The nature of geography and the Schaefer-Hartshorne debate - Martin, G.J. (Reflections on Richard Hartshorne's "The nature of geography', 1989)
The tendency by geographers to cast Hartshorne as either hero or villain in modern American geography is clearly represented in this essay considering the Hartshorne-Schaefer controversy, a dispute of almost mythical proportions in the modern history of American geography. Through analysis of unpublished and published documents, the author provides us with a wealth of historical information concerning the relation between the two antagonists and the events surrounding the publication of their methodological statements. The reportage has an additional, illocutionary impact that derives from the introduction of historical specificities into the discussion of mythologized events. The description and evaluation of the events surrounding this episode in American geography, especially its portrayal of spatial analysts in the uncharacteristic role of loyal sentimentalists, will probably add fuel to the dying embers of this controversy. -from Editors
Keywords: American geography; Hartshorne; R.; Schaefer; dept.egm; geographers; historical information; illocutionary impact; methodological statement; spatial analysts; ⛔ No DOI found